Empowering health cadres in managing maternal and child health in the Covid-19 pandemic era - Chahya Kharin Herbawani; Terry Y.R. Pristya; Ulya Qoulan Karima; Maharanti Maharanti; Elisabeth Kristina Ari Nugrahanti (Community Empowerment, 2021)
The covid-19 pandemic has hampered the access of mothers and children to optimal health services. The decreasing number of visits to maternal and child health services has created new nutrition and health problems. However, the Posyandu as one of the health services for mothers and children in several locations were forced to close during the covid-19 pandemic, such as Posyandu RW 07, Cipayung Village. The purpose of this community service is to increase the capacity of the integrated services post (Posyandu) cadres to cadres for maternal and child health responses during the covid-19 pandemic. Service activities are carried out through 3 stages of activity which was starting with discussions with partners about the importance of re-activating the Posyandu for infants and toddlers during the covid-19 pandemic, then increasing the capacity of health cadres for babies and toddlers health services, then handbook creation and evaluation. The method used combines several approaches, such as discussions, socialization, workshop, and evaluation. The result is an increase in the capacity of health cadres and the guidebooks for services and the Posyandu visits during the covid-19 pandemic.